Java for dummies quick reference - Lowe, Doug 1959- (John Wiley & Sons, 2012)
A reference that answers your questions as you move through your codingThe demand for Android programming and web apps continues to grow at an unprecedented pace and Java is the preferred language for both. Java For Dummies Quick Reference keeps you moving through your coding while you solve a problem, look up a command or syntax, or search for a programming tip. Whether you're a Java newbie or a seasoned user, this fast reference offers you quick access to solutions without requiring that you wade through pages of tutorial material. Leverages the true reference format that is organized with q.
Keywords: Java (Computer program language) -- Amateurs' manuals; World Wide Web; Internet; Java (Langage de programmation); Manuels d'amateurs; Web; COMPUTERS; Programming Languages; Java; Java (Computer program language); Handbooks and manuals